Analisis keberhasilan industri kecil dan dampaknya terhadap daya serap tenaga kerja di Kota Jambi - Widiyanti, Heni; Zulfanetti, Zulfanetti; Umiyati, Etik (Jurnal Paradigma Ekonomika, 2022)
Jambi Province became the second province in Indonesia whose small industrial businesses were minimally affected by COVID-19 in 2020 (BPS, 2020). Jambi City as a strategic location for the growth of small industries in Jambi Province. Therefore it is necessary to know the factors affecting the success of small industries. This study used primary and secondary data. Using ordinal logistic regression analysis to see the influence of entrepreneur characteristics, business characteristics, contextual variables on changes in profits and simple linear regression to analyze the influence of profit variables on the number of workers.